Quality Control in Survey Design: Evaluating a Survey of Educators’ Attitudes Concerning Differentiated Compensation - Kelly D. Bradley; Michael Peabody; Shannon O. Sampson (International Journal of Assessment Tools in Education)
This study utilized the Rasch model to assess the quality of a survey instrument designed to measure attitudes of administrators and teachers concerning a differentiated teacher compensation program piloted in Kentucky.  Researchers addressing potentially contentious issues should ensure their methods stand up to rigorous criticism.  The results indicate that the rating scale does not function as expected, with items being too easy to endorse.  Future iterations of this survey should be revised prior to release.  Recommendations for improvement are provided.